Morphological Diversity and Morphometric Analysis of Commercially Traded Siganus spp. (Baronang Fish) in Tarakan's Beringin Market - Gaffar, Syamsidar; Salwa, Salwa; Sumarlin, Sumarlin (Jurnal Harpodon Borneo, 2022)
This study aimed to investigate the morphological diversity and morphometric characteristics of commercially traded Siganus spp. (Baronang fish) in Tarakan's Beringin Market. A total of 100 fish specimens were collected from the market and analyzed using 23 morphometric measurements to identify differences in species and provide insights into their population structure. The measurements included total length, standard length, head length, head height, body height, caudal peduncle height, eye diameter, inter-eye distance, body width, and several other parameters related to fins and jaw length. The results showed a wide range of values for each morphometric parameter, suggesting a high degree of morphological variation among the sampled Baronang fish. For instance, the minimum and maximum total lengths were 15.07 cm and 22.17 cm, respectively, with an average of 10.84 cm and a standard deviation of 1.93. The head length ranged from 2.83 cm to 4.66 cm, with an average of 2.31 cm and a standard deviation of 0.46. Furthermore, the body height varied between 6.52 cm and 8.57 cm, with an average of 4.31 cm and a standard deviation of 0.53. These results, along with the other morphometric parameters, highlight the diverse morphological traits of Siganus spp. present in the Beringin Market. Comparisons with previous studies on Siganus spp. indicate that the morphological diversity observed in the present study is consistent with the known intraspecific variation within this genus. However, further research is required to determine if the observed differences are due to phenotypic plasticity, genetic differences, or a combination of both factors. This research contributes to a better understanding of the morphological diversity and morphometric characteristics of Siganus spp. in Tarakan's Beringin Market, which can be valuable for fisheries management, conservation efforts, and the sustainable use of this commercially important fish species. Future studies should explore the genetic diversity and population dynamics of Baronang fish to complement the findings of this study and further inform management strategies.